How do intellectual capital and Islamic work ethics affect SME business performance? / Sakinah Mat Zin and Engku Huda Mursyidah Engku Hassan Ashari - Mat Zin, Sakinah; Engku Hassan Ashari, Engku Huda Mursyidah (Universiti Teknologi MARA, Perlis, 2020)
This paper explores the effect of intellectual capital (IC) and Islamic Work Ethics (IWE) on Small and Medium Enterprise (SME) business performance. Based on a qualitative study, the results provide support to SME entrepreneurs to understand the effects of IC and IWE on business performance and facilitate them in making the right decision. The qualitative results were obtained from documents analysis and interview sessions. For the interview session, three entrepreneurs (regarded as the key informants) provided a deeper understanding on how IC and IWE had managed to influence SME Business Performance. SME entrepreneurs must realise on the need to maintain a competitive advantage and enhance the opportunity to create profitability through extracting value from IC and IWE. The originality of the paper regards the way it addresses simultaneously IC and IWE, such related concepts. Moreover, findings of this study suggest that SME entrepreneurs should extend practices of Islamic work ethics to employees, customers, vendors, partners and the communities by building a positive environment founded on trust and commitment.